A novel integrated wastewater recovery, clean water production and air-conditioning system. (15th September 2021) - Luqman, Muhammad; Al-Ansari, Tareq
Graphical abstract: Highlights: An integrated solution to wastewater recycling, clean water production and air-conditioning. Chilled air output at constant temperature and relative humidity irrespective of ambient conditions. Provides solution to the social perception regarding wastewater reuse. The solution is applicable globally and especially useful in hot and arid climates. Abstract: Ensuring water and energy security for the growing global population is a challenge that aggravates several folds if in water-scarce regions, accustomed to prevailing hot climates and coupled with the increasing per capita demand of these resources. Furthermore, in hot and arid regions, the largest portion of energy is consumed by air-conditioning in buildings. Similarly, fulfilling the water needs in water-scarce regions also consumes a large amount of energy. The consequence of this high energy and water demand are significant greenhouse gas emissions and other pollutants. In this context, this study presents an integrated solution to support water security by reclaiming wastewater, and energy security by shifting the air-conditioning load from electricity to low-grade thermal energy. Although the proposed system is globally applicable, it is specifically valuable in hot and arid climates. The system harnesses solar energy using Evacuated Tube Collectors (ETCs) and produces clean water and conditioned air. Besides ETCs, the system is composed of an absorption cooling system, air humidification unit, three pumps and a blower. The unique features of the proposed system include the production of conditioned air at constant temperature and humidity irrespective of the ambient environmental conditions and flexibility of 24 h operations through the TES integration, which decouples the system's operational energy demand from the available energy's supply. A comprehensive thermodynamic analysis is conducted, which includes the application of mass balance equations and 1st and 2nd laws of thermodynamics. In addition, the effects of ambient environmental conditions and the available energy on the system's performance are studied and found that the system can operate stably and continuously. At design conditions, with a solar field area of 1, 000 m 2, the system recycles approximately 900 L/day of wastewater and produces 1, 418 L/day of clean water. Moreover, considering 24 h of operations, the system provides 8.7 refr. tons of air-conditioning. The system's overall energy and exergy efficiencies are 14.4% and 0.7%, respectively. Furthermore, in the context of the social perceptions regarding wastewater reuse, a hydrogen cycle-based solution is also presented, which can produce approximately 560 L/day of socially acceptable water.